Effects and moderator of high-intensity interval training and moderate-intensity continuous training among children and adolescents with overweight or obese: a systematic review and meta-analysis - Zheng, Weihua; Yin, Mingyue; Guo, Yan; Liu, Haiyang; Sun, Jiaxin; Zhu, Ao; Zhong, Yuming; Xu, Kai; Li, Hansen; Piao, Shunzhe (Frontiers in Physiology, 2025)
ObjectivesThis meta-analysis aimed to synthesize current evidence and address inconsistencies in the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on children and adolescents with overweight or obesity. We sought to: (1) assess the effects of HIIT and MICT versus non-exercise controls; (2) compare HIIT and MICT directly; and (3) identify potential moderators through subgroup analyses.MethodsSystematic searches were conducted in PubMed, Web of Science, China National Knowledge Infrastructure, and CSTJ. Standardized mean differences (SMD) were calculated using a random-effects model. Subgroup and sensitivity analyses explored potential moderators.ResultsA total of 26 moderate-to-high-quality studies (Randomized controlled trials and non-RCT) involving 1,078 participants (765 males, 313 females; aged 9–19) were included. Compared with controls, HIIT significantly reduced fat mass (SMD = −0.69), waistline (SMD = −0.67), body weight (SMD = −0.81), diastolic blood pressure (diastolic blood pressure, SMD = −0.68), and improved VO2max (SMD = 2.06). moderate-intensity continuous training showed significant effects on BMI (SMD = −1.58), body weight (SMD = −0.59), DBP (SMD = −0.60), and VO2max (SMD = 1.26). HIIT outperformed MICT in improving VO2max (SMD = 0.81) and reducing systolic blood pressure (systolic blood pressure, SMD = −0.51). Subgroup analyses showed that HIIT yielded greater benefits than MICT in improving VO2max among overweight children, reducing SBP in obese male adolescents, and in programs involving more than three sessions per week.ConclusionHIIT was more effective than MICT in improving VO2max and reducing SBP, especially in specific subgroups. Running-based HIIT three times per week is recommended, while cycling may offer a safer alternative. Results should be interpreted cautiously due to limited subgroup data and potential bias.Prospero RegistrationCRD42024612098.